A TRANSMISSION PROBLEM FOR WAVES UNDER TIME-VARYING DELAY AND TIME-VARYING WEIGHTS - Nonato, Carlos A. S. (2022)
This manuscript focuses on in the transmission problem for one dimensional waves with time-varying weights on the frictional damping and time-varying delay. We prove global exis-tence of solutions using Kato's variable norm technique and we show the exponential stability by the energy method with the construction of a suitable Lyapunov functional.